Subcooled flow boiling in horizontal and vertical macro-channel under Earth-gravity and hyper-gravity conditions. (April 2019) - Vlachou, Maria C.; Lioumbas, John S.; Kostoglou, Margaritis; David, Kostantinos; Chasapis, Dimitrios; Schwarz, Christian; van Loon, Jack J.W.A.; Karapantsios, Thodoris D.
Graphical abstract: Highlights: Effect of hyper-g (1.8-9 times the Earth-g) depends on channel inclination. Hyper-g heat transfer coefficient at horizontal channel is ~10-15 % higher than 1-g. Hyper-g heat transfer coefficient at vertical channel is ~20-40 % lower than 1-g. Horizontal: buoyancy widens thermal boundary layer and promotes bubbles detachment. Vertical: buoyancy promotes bubbles sliding and enhances bubbles coalescence. Abstract: This is an experimental study on highly subcooled flow boiling of water for assessing the effect of gravitational acceleration on flow boiling heat transfer. The experiments are conducted in a macro-channel 3 mm high, 40 mm wide and 120 mm long at water mass fluxes of 330, 630 and 830 kg/m 2  s and heat fluxes in the range 200–900 kW/m 2 . Increased gravitational accelerations, from 1.8 to 9 times the Earth-gravity are achieved with the use of a ∼3 m radius centrifuge (Large Diameter Centrifuge, ESTEC/European Space Agency). Two distinct channel inclinations are examined; horizontal, where the gravitational acceleration is normal to the boiling surface, and vertical, where the gravitational acceleration is parallel to the boiling surface and opposite to flow direction. Experiments at hyper-gravity conditions show that for the horizontal channel inclination, flow boiling heat transfer coefficient increases, whereas for the vertical channel inclination it decreases. The observed deviations lie approximately between +15% and −40% from the Earth-g value. An interpretation of the present results is attempted based on the effect of liquid-phase natural and forced convection combined with the effect of buoyancy at vapor bubbles. The tendency of the heat transfer coefficient experimental data with respect to changes in gravitational acceleration allows the development of a gravity-modified version of the well-known two phase model of Liu-Winterton, by incorporating a linearly dependent gravity multiplier.